FOOD, CANNIBALISM, AND ANTI-ASIAN RACISM IN THE ERA OF COVID-19 - Griffin, Clare (Nazarbayev University School of Sciences and Humanities, 2020)
The second talk of our Fall 2020 speaker series will feature Dr. Clare Griffin, (Assistant Professor, Department of History, Philosophy, and Religious Studies Nazarbayev University), who will discuss “Food, Cannibalism, and Anti-Asian Racism in the Era of COVID-19”.
Keywords: Food; Cannibalism; Anti-Asian Racism; COVID-19; Pandemic; Humanities; Research Subject Categories::HUMANITIES and RELIGION